(untitled) (Academicia Globe: Inderscience Research, 2025)
The article analyzes the symbolic and philosophical aspects of images of nature in Marcel Proust’s work “In Search of Lost Time”. Nature in the work is not just a decorative background, but a philosophical concept closely related to human memory, the concept of time and the stream of consciousness. The author uses images of nature to connect the past and the present, as well as to express aesthetic and spiritual experiences. This article is devoted to highlighting the symbolism and philosophical aspects of nature.